Analisis Peningkatan Daya Saing Produk Melalui Manajemen Sumber Daya Manusia (Studi pada BPJS Kesehatan Cabang Bone) - Muhammad Ikram; Rusdiawan Rusdiawan (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to find out (1) how is the position of BPJS Health Bone Branch product competitiveness from five Branch Offices in South Sulawesi over the past three years? (2) how is the role of Human Resources BPJS Branch Bone Management in an effort to improve the position of product competitiveness?. Based on the objectives of the above research, the type of research used is field research using a qualitative approach. This study uses the method of observation, interviews, and documentation in collecting the required data. The collected data is then processed using the Descriptive Analysis analysis method. The results of the study show the position of Branch Bone BPJS Health product competitiveness from 2014-2016 has never occupied the first position of the five Branch Offices in South Sulawesi, but has increased in 2015 from third to second and in 2016 still in second place. And the role of Human Resource BPJS Kesehatan Bone management in an effort to support increased product competitiveness is divided into three roles: (1) Role of Administration, namely by implementing competency-based performance management system applications in every employee activity, (2) Operational Role, namely many are oriented towards training and development as well as employee competency systems which can be seen from a number of training activities that are always carried out by BPJS Health which leads to improving employee competencies, and (3) Strategic Roles, namely implementing talent management that aims to get employees with high employment .